Interaction between intra-continental sedimentary basins and small-volume monogenetic volcanism: Argamasilla and Calzada-Moral basins, Campo de Calatrava Volcanic Field, Spain - Herrero-Hernández, A.; López-Moro, F.J.; Gómez-Fernández, F.; Martín-Serrano, A. (Journal of Iberian Geology, 2012)
We study the volcaniclastic lithofacies interbedded between siliciclastic and carbonate sediments of Cenozoic-Quaternary age (8.7 Ma to 7,000 BP) in Argamasilla and Calzada-Moral basins (Central Spain). The siliciclastic and carbonate deposits correspond to fluvio-lacustrine sedimentary environments. The volcanic materials consist of primary and reworked volcaniclastic successions sourced from the Campo de Calatrava Volcanic Field. Pyroclastic deposits are related to monogenetic and small-volume volcanic centres, such as scoria cones, tuff rings and maars, corresponding to Strombolian and phreatomagmatic eruptive styles. Taking into account sedimentological constraints seven volcaniclastic lithofacies were distinguished. Type A corresponds to subaerial pyroclastic fall deposits, as is inferred by the common disorganization of the deposit, their breccia-like aspect with presence of large bombs, poor sorting and lack of tractional sedimentary structures. Types B1, B2, B3 and B4 have different volcanic sources and are interpreted to be the product of low-density (dilute) pyroclastic surges, with textural features indicative of fluctuations in flow regime. This interpretation is based on the fabric and grain size of pyroclasts, together with the size and geometry of the internal sedimentary structures. Type C represents a secondary volcanic deposit related to volcanic sediments reworked by transitional hyperconcentrated flows and dilute fluvial processes, having subsequently accumulated in braided fluvial systems. Finally, the Type D is interpreted as an intra-maar scoria/spatter cones related to the development of maars. The most important factors that determined the sedimentation in these basins were orientation of basement faults, paleogeographic and sedimentological controls, style of eruption and volcaniclastic lithofacies type.